EKSISTENSI LEKSIKON MAKANAN TRADISIONAL KHAS MUNA BERBAHAN DASAR JAGUNG DAN UBI KAYU PADA REMAJA SUKU MUNA (KAJIAN EKOLINGUISTIK) - Sahur Saerudin; Nurjannah (Program Studi Sastra Indonesia Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
This research focuses on the existence of Muna traditional food lexicon made from corn and cassava. This research was motivated by the development of modern culinary today which began to shift traditional food. This condition has an impact on the existence of traditional food lexicon which is increasingly endangered. Based on that reason, this research aims to describe the existence of traditional Muna food lexicon made from corn and cassava in Muna youth. The method in this research is descriptive quantitative and qualitative. The result of this research is described in the form of level of existence of Muna traditional food lexicon made from corn and cassava in the form of percentage. Based on the results of research on 50 respondents, the existence of the lexicon of traditional Muna food made from corn and cassava is at the level of 70%. The percentage results show that the lexicon of traditional Muna food made from corn and cassava still exists among teenagers in Muna district. Keywords: Lexicon, Traditional Food, Muna